The Inducible microRNA-21 Negatively Modulates the Inflammatory Response in Teleost Fish via Targeting IRAK4 - Chu, Qing; Yan, Xiaolong; Liu, Lihua; Xu, Tianjun (Frontiers in Immunology, 2019)
Eradication of bacterial infection requires timely and appropriate immune and inflammatory responses, but excessive induction of inflammatory cytokines can cause acute or chronic inflammatory disorders. Thus, various layers of negative regulators and mechanisms are needed to ensure maintenance of the homeostasis for immune system. miRNAs are a family of small noncoding RNAs that emerged as significant and versatile regulators involved in regulation of immune responses. Recently, the molecular mechanisms of miRNA in host-pathogen interaction networks have been extensively studied in mammals, whereas the underlying regulatory mechanisms in fish are still poorly understood. In this study, we identify miR-21 as a negative regulator of the teleost inflammatory response. We found that lipopolysaccharide and Vibrio anguillarum significantly upregulated the expression of fish miR-21. Upregulated miR-21 suppresses LPS-induced inflammatory cytokine expression by targeting IL-1 receptor-associated kinase 4 (IRAK4), thereby avoiding excessive inflammatory responses. Furthermore, we demonstrated that miR-21 regulates inflammatory responses through NF-κB signaling pathways. The collective findings indicate that miR-21 plays a regulatory role in host-pathogen interactions through IRAK4-mediated NF-κB signaling pathway.